2007
DOI: 10.4161/cc.6.3.3800
|View full text |Cite
|
Sign up to set email alerts
|

Key role of p63 in BMP-4-Induced Epidermal Commitment of Embryonic Stem Cells

Abstract: In vivo studies, transgenic and knock-out mice have demonstrated that p63 isoforms play pivotal roles in ectodermal and epidermal development but their respective function remains highly controversial. Since embryonic stem (ES) cells can be differentiated into many cell types, they represent an effective tool to recapitulate in vitro the main steps of embryonic development. We recently reported the efficient derivation of ectodermal and epidermal cells from murine ES cells and clarified the function of BMP-4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 17 publications
2
52
2
1
Order By: Relevance
“…1G). Epidermal markers, the cytokeratins Krt8 (K8) and Krt18 (K18), were previously reported to be expressed in the single-layer ectodermal cells from E8.5 (Aberdam et al, 2007b). However, our data show that K8 and K18 expression is detectable in the anterior side as early as E7.5 (Fig.…”
Section: Dynamic Patterns Of Gene Expression During Ectoderm Formationcontrasting
confidence: 55%
“…1G). Epidermal markers, the cytokeratins Krt8 (K8) and Krt18 (K18), were previously reported to be expressed in the single-layer ectodermal cells from E8.5 (Aberdam et al, 2007b). However, our data show that K8 and K18 expression is detectable in the anterior side as early as E7.5 (Fig.…”
Section: Dynamic Patterns Of Gene Expression During Ectoderm Formationcontrasting
confidence: 55%
“…We recently demonstrated that the exogenous expression of ⌬Np63 is necessary to differentiate murine K8/K18 ϩ ectodermal cells into K5/K14 ϩ keratinocytes [17]. Accordingly, IT1 cells, transduced with a lentivirus expressing ⌬Np63, became K14-positive cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, TAp63 isoforms have not been detected by in situ hybridization or immunoblot; thus TAp63 protein levels appear to be barey detectable [13,20]. Studies in ES-derived cells shows that BMP-4 treatment, leading to the ectodermal fate, induces Np63, while exogenous expression of the Np63 isoform in ES-derived ectodermal cells efficiently leads to their differentiation into keratinocytes [21].…”
Section: Trp63 Gene Organization and P63 Protein Structurementioning
confidence: 99%